Shield Maidens, Fashy Femmes, and TradWives: Feminism, Patriarchy, and Right-Wing Populism - Love, Nancy S. (Frontiers in Sociology, 2020)
Although media images typically present the alt right as a “manosphere,” white women continue to participate actively in white supremacist movements. Alt right women's presence as “shield maidens,” “fashy femmes,” and “trad wives” serves to soften and normalize white supremacy, often in ironic and insidious ways. In this essay, I examine the continued investment of white women in these traditional sex/gender roles espoused by the alt right. While feminism has done much to liberate women, I conclude that the images of women as Moms circulating in mainstream politics today suggest that white supremacy and white women's complicity in it has yet to be overcome.